Structural Stability for a Coupled System of Wave Plate Type - Jincheng Shi; Ze Wang; Yuanlong Chen (Discrete Dynamics in Nature and Society)
This paper focuses on the spatial properties of a coupled system of wave plate type in a two-dimensional pipe. Using the technique of differential inequality and the method of energy estimation, the effect of the coefficient λ is established.